Effects of vitamin D receptor inactivation on the expression of calbindins and calcium metabolism - Li, Y C; Bolt, M J; Cao, L P; Sitrin, M D (American journal of physiology: endocrinology and metabolism, 2001)
Hypocalcemia, rickets, and osteomalacia are major phenotypic abnormalities in vitamin D receptor (VDR)-null mice. In an attempt to understand the abnormal regulation of calcium metabolism in these animals, we examined the expression of calbindins (CaBP) as well as calcium handling in the intestine and kidney of VDR null mice. In adult VDR-null mice, intestinal and renal CaBP-D9k expression was reduced by 50 and 90%, respectively, at both the mRNA and protein levels compared with wild-type littermates, whereas renal CaBP-D28k expression was not significantly changed. Intestinal calcium absorption was measured by the rate of (45)Ca disappearance from the intestine after an oral dose of the isotope. (45)Ca absorption was similar in VDR-null and wild-type mice, but the amount of (45)Ca accumulated in the serum and bone was 3-4 times higher in wild-type mice than in VDR-null mice. Despite the hypocalcemia, the urinary excretion of calcium in VDR-null mice was not different from that in wild-type mice. Moreover, 1 wk of a high-calcium diet treatment that normalized the serum ionized calcium level of VDR-null mice increased the urinary calcium level of these mutant mice to twofold higher than that of wild-type mice on the same diet, suggesting impaired renal calcium conservation in VDR-null mice. These data demonstrate that renal CaBP-D9k, but not CaBP-D28k, is highly regulated by the VDR-mediated action of 1,25-dihydroxyvitamin D(3). Furthermore, the results also suggest that impaired calcium conservation in the kidney may be the most important factor contributing to the development of hypocalcemia in VDR-null mice, and CaBP-D9k may be an important mediator of calcium reabsorption in the kidney.